Statistical analysis of academic performance among pupils in primary schools. a yardstick for an unbiased decision - making - Omebo, D.M.O.; Emmanuel†, A.Y.; Ailobhio‡§, T.D.; Fanen‡**, G.I. (International Journal of Mathematical Analysis and Modelling, 2023)
This paper is an extract of the research findings that was carried out in Ofu local government area of Kogi state in 2021 which was used to resolve the conflict that broke out as a result of the proposal to establish Government model Science College by the Kogi state Government. The bone of contention then was either to establish model boys’ college or model girls’ college in the local government. This necessitated the research to find out if performance depends on sex or not. An analysis of variance for categorical data (CATANOVA) was used in carrying out the test. It was discovered that performance depends on sex, and that male pupils performed better than the female pupils. Hence, Government boys model college was recommended. All the findings were based on the performance of male and female pupils in primary six using common entrance examination results for 2019 since there was no common entrance examination for 2020 due to covid-19 pandemic.